Targeting the MDSCs of Tumors In Situ With Inhibitors of the MAPK Signaling Pathway to Promote Tumor Regression - Yu, Jiayun; Li, Hanwen; Zhang, Zongliang; Lin, Weimin; Wei, Xiawei; Shao, Bin (Frontiers in Oncology, 2021)
Myeloid-derived suppressor cells (MDSCs) are one of the major components of the tumor microenvironment. Evidence has shown differences in the functions and fates of MDSCs in the tumor tissue and the periphery. However, the exact mechanism that regulates MDSC function has not been completely clarified. In this study, we performed RNA sequencing of MDSCs derived from the spleen and tumor. Based on the results of our RNA-seq analysis, mitogen-activated protein kinases (MAPK) were significantly increased in tumor polymorphonuclear MDSCs (PMN-MDSCs) and monocytic MDSCs (M-MDSCs). Subsequently, 3 major MAPK pathways, including extracellular signal-regulated protein kinases (ERK), p38 and c-Jun NH2-terminal kinases (JNK), were studied to analyze the role of MAPKs in MDSCs. The ERK 1/2 inhibitor SCH772984 and the JNK inhibitor SP600125 significantly increased the apoptosis of both PMN-MDSCs and M-MDSCs in vitro. In addition, SCH772984 exerted a strong effect on inhibiting tumor growth. The flow cytometry analysis showed significant increases in the ratio of M1:M2 tumor-associated macrophages, meanwhile the number of CD4+, CD8+, CD4+CD69+ and CD8+CD69+ lymphocytes were increased after SCH772984 treatment. Our findings established the effect of MAPKs on the tumor microenvironment via MDSCs and may facilitate the development of new antitumor strategies.